2020
DOI: 10.1371/journal.pone.0242096
|View full text |Cite
|
Sign up to set email alerts
|

Visual estimates of blood loss by medical laypeople: Effects of blood loss volume, victim gender, and perspective

Abstract: A severe hemorrhage can result in death within minutes, before professional first responders have time to arrive. Thus, intervention by bystanders, who may lack medical training, may be necessary to save a victim’s life in situations with bleeding injuries. Proper intervention requires that bystanders accurately assess the severity of the injury and respond appropriately. As many bystanders lack tools and training, they are limited in terms of the information they can use in their evaluative process. In hemorr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 34 publications
8
15
0
1
Order By: Relevance
“…Data is stored on a secure server. The first study using SABLE was conducted in a lab setting using American college students (Phillips et al, 2020a). Consistent with previous research, Phillips et al found that participants overestimated small volumes of blood loss and underestimated large volumes, suggesting that medical laypeople demonstrate the same pattern of results as medical professionals and SABLE is an effective research tool.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…Data is stored on a secure server. The first study using SABLE was conducted in a lab setting using American college students (Phillips et al, 2020a). Consistent with previous research, Phillips et al found that participants overestimated small volumes of blood loss and underestimated large volumes, suggesting that medical laypeople demonstrate the same pattern of results as medical professionals and SABLE is an effective research tool.…”
Section: Introductionmentioning
confidence: 53%
“…A common finding in research on visual blood loss estimation is that small amounts of blood are overestimated, and large amounts underestimated (Al-Kidri et al, 2014;Frank et al, 2010;Hancock et al, 2015;Phillips et al, 2020a). However, there are relatively few studies of how medical laypeople perceive blood loss.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It revealed that laypeople overestimated small volumes of blood loss (50–200 ml) and underestimated larger volumes (400 −1900 ml) [ 48 ]. A similar situation happened with clinicians, regardless of their training and skills [ 49 ]. Thus, the visual estimation of blood loss is usually inaccurate; therefore, it is an inherent limitation of all triage systems.…”
Section: Discussionmentioning
confidence: 94%
“…their training and skills [49]. Thus, the visual estimation of blood loss is usually inaccurate; therefore, it is an inherent limitation of all triage systems.…”
Section: Plos Onementioning
confidence: 99%